Implementation of transformational leadership and organizational culture in improving the quality of education in public elementary schools in Walantaka District, Serang City - Uyu Wahyudin; Ahmad Mukhlis; RR Andriani (Jurnal Bisnis Mahasiswa, 2026)
Purpose – This research is motivated by the importance of improving the quality of basic education through effective leadership of school principals and a conducive organizational culture. Public Elementary Schools in Walantaka District, Serang City, face challenges in improving the quality of learning, necessitating the implementation of transformational leadership integrated with a positive organizational culture. This study aims to describe and analyze the implementation of transformational leadership and organizational culture to improve the quality of education, particularly by strengthening teacher professionalism, learning innovation, and active student involvement. Design/methodology/approach – A qualitative approach was employed, with data collected through semi-structured in-depth interviews, document analysis, and field observations involving 75 purposively selected participants. Data were analyzed using the six-phase thematic analysis framework (Braun & Clarke, 2006). Findings – The results reveal five main themes: visionary and exemplary leadership, motivational and innovative teaching, individualized professional support, collaborative organizational culture, and positive impact on student engagement. Transformational leadership—through a clear vision, inspirational motivation, individualized attention, and learning innovation—drives significant improvements in teaching quality. Research limitations – This study is limited to theoretical literature analysis and does not involve primary empirical data collection; therefore, causal relationships among variables cannot be statistically verified, and the findings have not been tested on a specific population sample. Implications – A collaborative, disciplined, and professional organizational culture strengthens its impact, resulting in continuous improvement in education quality. The implementation of transformational leadership, supported by a positive organizational culture, contributes significantly to improving the quality of education at State Elementary Schools in the Walantaka District, Serang City. Originality – A unique contextual finding is the role of the local gotong royong (collective cooperation) cultural value as an organic amplifier of leadership effects.